Electrically Reconfigurable 3D Spin‐Orbitronics. (6th December 2020) - Dong, Yiqing; Xu, Teng; Zhou, Heng‐An; Cai, Li; Wu, Huaqiang; Tang, Jianshi; Jiang, Wanjun
Abstract: The explosive demands of storage capacity and the von Neumann bottleneck of modern computer architectures trigger many innovations in information technology. Amongst them, nonvolatile spintronics attract considerable attentions for which can embed the computation capability into memory, enable neuromorphic, and probabilistic computing. These exciting progresses typically rely on the manipulation of the relative magnetization orientations of two magnetic layers. By extending to 3D spintronic architectures made of multiple magnetic layers ( n ), the exponentially increased 2 n magnetic states can provide ample opportunities for implementing novel spintronic functionalities. Here, through building perpendicularly magnetized 3D spin‐orbitronic architectures – [Pt/Fe1− x Tb x /Si3 N4 ] n multilayers, it is demonstrated the electrical programing of 2 n memory states via current‐induced spin–orbit torques (SOTs), and the accompanied reconfigurable multifunction in‐memory logic features in a single four‐terminal Hall device. Further, an electrical readout of these 2 n states, together with the implementation of Boolean logic gates and digital circuitry such as 2–4 and 3–8 decoders, are successfully conducted. More complex logic circuits are also envisioned. The experiments thus substantiate 3D spin‐orbitronic structures as a promising platform for exponentially boosting the storage capacity and accommodating in‐memory computing that can be important for promoting the emerging 3D nanospintronics. Abstract : In a single 3D spin‐orbitronic cell made of [Pt/Fe1− x Tb x /Si3 N4 ] n multilayer, the electrical programing of 2 n memory states via current‐induced spin–orbit torques, and the accompanied reconfigurable multifunction in‐memory logic features are demonstrated.